Effects of temperature shock on the survival of different life stages of large yellow croaker (Larimichthys crocea) by simulated power plant cooling water - Tian, Sujie; Zhou, Konglin; Liao, Yibo; Tang, Yanbin; Liu, Qinghe; Zhang, Rongliang; Shou, Lu; Zeng, Jiangning (Frontiers in Marine Science, 2022)
Seawater temperatures have increased with global climate change. Coolant water discharged from coastal nuclear power-generating and coal-powered plants, coupled with already increasing seawater temperatures, can adversely affect local fish communities. A sudden drop in temperature caused by the winter shutdown of power plants can also affect fish health and behavior. To assess the effects of temperature change on fish populations, we subjected early life stages of the once commercially important large yellow croaker (Larimichthys crocea) to various water temperature experiments. Fertilized eggs showed the highest hatching rate at 23.4°C and the lowest rate of deformity in hatched larvae at 23.0°C. We determined the incipient lethal temperature for each life stages using derivation models. Ranges between the upper and lower incipient lethal temperatures increased during development from yolk-sac larvae to juveniles, especially in response to cold shock, indicating that later developmental stages in this species are more tolerant of temperature fluctuations. However, thermal tolerance is not solely determined by life stage. Our results suggest that rapid changes in seawater temperature caused by power plant coolant water discharges may significantly affect early developmental stages of fish. Critical thermal maximum tests indicate that the seawater heating rate is significantly negatively correlated with survival time and affects the critical thermal maximum value of L. crocea. On the basis of our determination of incipient lethal temperatures, emergency measures could be taken to avoid adverse economic and ecological impacts due to changes in seawater temperature caused by coolant water discharges.